Wage effects of U.S. service offshoring by skills and tasks - Julia Püschel (FIW - Research Centre International Economics, 2013)
In this paper, I estimate the impact of service offshoring on the real wages of U.S. workers by controlling for workers' skill levels and the offshoring susceptibility of different tasks. Matching individual-level wage data with input-output tables over the period from 2006 to 2009, I am further able to account for unobservable individual-level heterogeneity. The results from a Mincerian wage regression indicate that within skill groups, the impact of service offshoring on real wages depends on the task content of the respective occupation. The real wages of medium- and high-skilled workers employed in the least offshorable occupations were positively affected by service offshoring. However, within the groups of medium- and high-skilled workers, service offshoring negatively affected the real wage of the most tradable occupations.
Keywords: F14; F16; J31; F20; 330; Offshoring; services; tasks; wages